The Membrane-Proximal Region of C–C Chemokine Receptor Type 5 Participates in the Infection of HIV-1 - Tan, Yue; Tong, Pei; Wang, Junyi; Zhao, Lei; Li, Jing; Yu, Yang; Chen, Ying-Hua; Wang, Ji (Frontiers in Immunology, 2017)
The initial infection and transmission of HIV-1 requires C-C chemokine receptor type 5 (CCR5). Here, we report that the membrane proximal region (MPR, aa 22-38) of CCR5 participates in the infection of HIV-1. First, MPR-specific antibodies elicited in mice dose-dependently inhibited the infection of CCR5-tropic HIV-1. Second, substituting MPR with the same region from other co-receptors significantly impaired HIV-1 infection, while the key residues identified by alanine scanning mutagenesis formed an exposed leucine zipper-like structure. Moreover, a peptide derived from MPR could block the infection of a number of HIV-1 strains only before the formation of gp41 six-helix bundle, coincide with the early interaction between CCR5 and the gp120 protein during HIV-1 infection. These promising results ensured the potential of this previously uncharacterized domain as a starting point for the development of antiviral drugs, blocking antibodies and HIV vaccines.